PTU-133 Goblet Cell Carcinoma of the Appendix: Acute vs Chronic Presentations. (4th June 2013) - Basuroy, R; Ngu, A; Mills, L; El-Mahallawi, H; Cecil, T; Ramage, J K
Abstract : Introduction: Goblet Cell Carcinomas (GCC) are a rare neuroendocrine tumour (NET) of the appendix. The experience of a National Specialist Centre's for pseudomyxoma peritonei (cytoreductive surgery) and two regional NET services with patients with GCC are presented. Methods: A retrospective audit was performed of patients with histologically proven GCC collated from histology, NET and cytoreductive surgery databases. Mortality rates (%) for subgroups were calculated. Results: 16 patients (female = 9) were included for analysis with median age at diagnosis of 58 years (range, 25.5–71.8). The mortality rate was 25% (n = 4) associated with median survival of 22 months (range, 9–72) following diagnosis. The most common symptoms were acute appendicitis-like (62.5%), chronic abdominal pain (50%), bowel obstruction (25%) and chronic diarrhoea (12.5%). Patients presenting with acute appendicitis-like symptoms had the lowest mortality rate at 10%. Bowel obstruction, chronic abdominal pain and chronic diarrhoea were associated with mortality rates of 50%, 38% and 50% respectively. Completion right hemicolectomy (n = 10) was associated with decreased mortality (22% vs 40%). Bilateral salphingo-oophrectomy (n = 5) was associated with increased mortality (66% vs 0%). The mortality rate associated with chemotherapy (n = 6) and cytoreductive surgery (n = 4) was 17% and 50% respectively. Conclusion: Patients with GCC who present acutely have better outcomes than those with chronic symptoms suggesting different disease processes. Performing a completion right hemicolectomy is associated with benefit, while the role of BSO is less clear. Disclosure of Interest: None Declared